2007
DOI: 10.1007/s00535-007-2080-6
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of intestinal amoebiasis by using nested polymerase chain reaction-restriction fragment length polymorphism assay

Abstract: Nested PCR-RFLP was useful for the specific detection of E. histolytica, E. dispar, and E. moshkovskii in stool samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 36 publications
(33 reference statements)
2
22
0
Order By: Relevance
“…Several reports suggest that mixed infections of E. histolytica and E. dispar are not uncommon (Acuna-Soto et al, 1993, Beck et al, 2008, Haque et al, 1998a, Khairnar et al, 2007, Zaki et al, 2003a. Similarly, E. moshkovskii infections have often been found to be associated with E. dispar and/or E. histolytica infections , Beck et al, 2008, Fotedar et al, 2008, Khairnar et al, 2007, Parija & Khairnar, 2005.…”
Section: Infections With Multiple Genotypesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several reports suggest that mixed infections of E. histolytica and E. dispar are not uncommon (Acuna-Soto et al, 1993, Beck et al, 2008, Haque et al, 1998a, Khairnar et al, 2007, Zaki et al, 2003a. Similarly, E. moshkovskii infections have often been found to be associated with E. dispar and/or E. histolytica infections , Beck et al, 2008, Fotedar et al, 2008, Khairnar et al, 2007, Parija & Khairnar, 2005.…”
Section: Infections With Multiple Genotypesmentioning
confidence: 99%
“…Similarly, E. moshkovskii infections have often been found to be associated with E. dispar and/or E. histolytica infections , Beck et al, 2008, Fotedar et al, 2008, Khairnar et al, 2007, Parija & Khairnar, 2005. Use of species-specific PCR amplification can usually detect and differentiate multiple infections, at least where distinct primers are used for each species.…”
Section: Infections With Multiple Genotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, metronidazole is prescribed for the treatment of amoebiasis and taken as drug of choice (Tasanor, 2007;Gupta, 2004;Khairnar, 2007) but studies have shown that it is not effective against the cyst, as it is rapidly absorbed from the lumen (Powell, 1969). The present recommendations are to combine this drug with some luminal amoebicidal like paromycin or diloxanide furoate.…”
Section: Discussionmentioning
confidence: 99%
“…In the Indian subcontinent, the prevalence of intestinal amoebiasis among hospitalized patients was found to be around 11.7% using microscopy. However, using molecular biology tools such as PCR, E. histolytica was shown to be in 3.5% of those infected (Khairnar et al, 2007). In another endemic country such as Bangladesh and using ELISA antigen detection kits, E. histolytica prevalence was found to be 4.2% among children living in the urban slums of Dhaka ).…”
Section: Epidemiology Of Amoebiasis and Its Occurrence In The Era Of mentioning
confidence: 99%